Keabsahan Akta Pendirian Perseroan Terbatas Terkait Tidak Dicantumkannya Masa Jabatan Direksi - Theresia, Christine; Putra, Mohamad Fajri Mekka (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
There are numerous ventures that are existed in the business world one of the example is Limited Liability Companies. The establishment of a Limited Liability Company has own terms set forth in the law number 40 of 2007 concerning Limited Liability Companies The articles of association are the goals of the company. Limited companies must consider a special budget in accordance with UUPT 40/2007 so as not to cause problems for interested parties.Limited companies organs make up of the General Meeting of Shareholders, the Board of Directors, and the Board of Commissioners. The Board of Directors is the most important organ in the Limited Liability Company because the Board of Directors may represent the Limited Company inside and outside the court. This important role has consequences on the importance of determining the members of the Board of Directors as stated in the Articles of Association whether or not it is authorized to represent a Limited Liability Company. The Articles of Association governing an unspecified term of office of the Board of Directors are contrary to the Law of Limited Liability Companies. This resulted in the law provision being null and void.